Selection of Suitable Media for In vitro Development of Seedling in an Ornamental Orchid: Doritis pulcherrima Lindl. (Plant Tissue Culture and Biotechnology, 2026)
Doritis pulcherrima is an important ornamental orchid due to its aesthetic appeal and wide usage in hybrid breeding. This study evaluated several nutrient-rich growth media including MS, ½MS, Knudson’s C (KC), KC with added peptone, Vacin and Went (VW), Lindemann Orchid (LO), Mitra Orchid (MT), and Gamborg’s medium (GM) to determine the most suitable one for in vitro multiplication of protocorm-like bodies (PLBs) derived from asymbiotic seed suspension cultures. Development of the plantlets assessed over four and eight weeks based on the number of leaves, root, and plantlet length. Among the various media used KC showed the most vigorous growth with highest number of leaves (7.4 ± 1.356), roots (4.8 ± 1.469), and plantlet length (2.46 ± 0.454) after eight weeks of culture. In contrast, VW caused tissue browning, while KC with peptone slowed early growth, highlighting KC as the most effective media for in vitro growth and propagation of D. pulcherrima.Plant Tissue Cult. & Biotech. 36(1): 13-23, 2026 (June)